THE EFFECT OF CUSTOMER RELATIONSHIP MARKETING AND TOTAL QUALITY MANAGEMENT ON CONSUMER BUYING INTEREST AT THE ANGELIA MELY SARUDIK STORE, CENTRAL TAPANULI REGENCY - Zunaidar; Rifka Hadia Lubis; Indra Setiawan Hutabarat (Cattleya Darmaya Fortuna, 2025)
One of the goals of marketing is to stimulate the emergence of a desire to buy. Buying interest will arise on its own, if the company is able to maintain and improve relationships with consumers and is able to provide quality products or services that meet the needs and satisfaction of the consumer market continuously. The purpose of this study is to determine the influence of customer relationship marketing and total quality management on consumer buying interest in Angelia Mely Sarudik Store, Central Tapanuli Regency. The type of study used associative explanatory with a sample of 63 people and was analyzed using multiple linear regression analysis. The results of the study found that the R Square determination coefficient was 0.564, meaning that 56.4% of consumer buying interest was influenced by customer relationship marketing and total quality management. While the remaining 43.6% can be influenced by other factors that are not discussed in this study. Customer relationship marketing has a positive and significant effect on consumer buying interest, it is known that the tcal value is 2,738 > the ttable value is 1,999 (2,738 > 1,999). Total quality management has a positive and significant effect on consumer buying interest. It is known that the t-count value is 5.703 > the ttable value is 1.999 (5.703 > 1.999). The results of the simultaneous test obtained by Fitutung (38.829) were greater than Ftabel (3.15) which means that customer relationship marketing and total quality management together have a positive effect on consumer buying interest. The regression equation is Y = 4.019 + 0.276 X1 + 0.610 X2 showing an increase in consumer buying interest after being influenced by customer relationship marketing and total quality management in a positive direction.